Violent behavior among military reservists. Issue 3 (24th October 2016) - Kwan, Jamie; Jones, Margaret; Hull, Lisa; Wessely, Simon; Fear, Nicola; MacManus, Deirdre
Abstract : Large numbers of British and American Reservists have been deployed to operations in Iraq and Afghanistan. Little is known about the impact of deployment and combat exposure on violent behavior in Reservists. The purpose of this study was to determine the prevalence of self‐reported violent behavior among a representative sample of United Kingdom Reservists, the risk factors associated with violence and the impact of deployment and combat exposure on violence. This study used data from a large cohort study of randomly selected UK military personnel and included Reservists who were in service at the time of sampling ( n = 1710). Data were collected by questionnaires that asked about socio‐demographic and military characteristics, pre‐enlistment antisocial behavior, deployment experiences, post‐deployment mental health, and self‐reported interpersonal violent behavior. The prevalence of violence among Reservists was 3.5%. Deployment was found to be a risk factor for violent behavior even after adjustment for confounders. The association with violence was similar for those deployed in either a combat role or non‐combat role. Violence was also strongly associated with mental health risk factors (PTSD, common mental disorders, and alcohol misuse). This study demonstrated higher levels of self‐reported post‐deployment violence in UK Reservists who had served in either Iraq or Afghanistan. Deployment, irrespective of the role was associated with higher levels of violent behavior among Reservists. The results also emphasize the risk of violent behavior associated with post‐deployment mental health problems. Aggr. Behav. 43:273–280, 2017. © 2016 Wiley Periodicals, Inc.